Menjalin Harmoni di Tengah Keberagaman di Desa Lagan Kecamatan Semidang Lagan Kabupaten Bengkulu Tengah - Pebrian Richkardo; Siana Resitawati; Sindi Kelaudia Utami; Ahmad Syarifin (MENYALA: Jurnal Pengabdian Masyarakat, 2024)
This article examines the dynamics of brotherhood in the context of racial, ethnic, cultural, and religious diversity in Desa Lagan, Semidang Lagan District, Central Bengkulu Regency. Using a qualitative approach, the study explores how the community in the village manages and balances their cultural and belief differences to create social harmony. Findings indicate that despite significant differences in these aspects, the people of Desa Lagan have successfully established close relationships through tolerance, mutual respect, and collaborative practices in traditional activities. This article contributes to the understanding of social mechanisms that support brotherhood amidst diversity and offers insights for developing models of intergroup relations in multicultural societies